PENDIDIKAN ANAK SUPUTRA SEBAGAI UPAYA DALAM MENINGKATKAN MUTU GENERASI MUDA HINDU - Nyoman Kiriana; Made Sujanayasa; Ni Nyoman Sri Widiasih (UHN IGB Sugriwa Denpasar, 2023)
The moral decline that is occurring among the younger generation today has led to the importance of the education of the son of a son who can be actualized through the ideals of educating the younger generation of Hindus. Where the character that grows in a child is initially formed from the environment. Educating children at this time of course has to adapt to changing times, such as instilling character in children through the use of digital technology that can help children think creatively. If the role of parents is not optimal since the child is small, then it is possible for a child when he grows up to be a teenager to do something that violates the rules of norms and ethics. This becomes very important with the impact of information media, namely television broadcast programs which are considered to provide less educational value for adolescents than their moral values. The education needed in educating children is not only academic education but also spiritual education so that children can face various problems and challenges in life. The education of Suputra children is very important to be carried out by parents in realizing a quality Hindu young generation who have a high leadership spirit.